Analysis of the treatment of había cantado in instructional materials of Spanish as a Foreign Language. Description, use and interrelations. - García Manga, María Carmen (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The aim of this article is to analyze the treatment of the pluperfect indicative tense in a corpus of 55 grammars and manuals of SFL. We verify the diversity of definitions and uses that are mentioned in the different works. Thus, we determine how its didactic treatment is proposed based on the analysis of the terminological variation of its denominations, the definitions and uses and interrelationships established with other verbal tenses and the presence of temporary adjuncts, without forgetting the exemplification used to carry out its illustration. As a result, not only the relative and relational nature of this verbal form is verified, but also the low metalinguistic load existing in grammars and manuals of SFL, especially in manuals belonging to the communicative approach. We start from the fact that in the teaching-learning of Spanish it is essential to attend to the form (Long, 1991 and 1997), so that linguistic and grammar of verb knowledge and metalinguistic reflection will be decisive in the success of the learning process